OLIGOPOLI DI NEGARA DEMOKRASI: PRAKTEK DAN KEPENTINGAN EKONOMI POLITIK MEDIA MASSA DI AUSTRALIA - Anna Yulia Hartati; Yusmita Wahyuni (Universitas Wahid Hasyim Semarang, 2021)
This article discusses the practice of Australian mass media oligopoly. The mass media in Australia is only controlled by a handful of wealthy businessmen, so it can be said that in the context of mass media ownership there is a very oligopolistic system. Media in Australia has developed in addition to economic factors, as well as political factors which make it difficult for interest groups and pressure groups in Australia to undermine their strength. the wall of the mass media oligopoly in Australia. This oligopoly is growing due to existing political factors, such as the granting of permits to make television stations to certain companies. Moreover, as longtime players, the media kings in Australia have established an establishment that is very difficult to disrupt, both in an economic context and in a political context. Monopoly is the main enemy of democracy. Even though the democratic life of the Australian people has been cultured, if the free choice is limited, then democracy is not a true form of democracy. A democracy whose continuity and products are directed by the holders of capital and power. Keywords: oligopoly practice, Australian mass media, king of media